Implementation Of The Analytical Hierarchy Process Method For Admission Of Scholarships At Smk Dharma Patra - Hilda Auliah Lubis; Nurhayati; Siswan Syahputra (International Journal of Health Engineering and Technology, 2022)
Scholarships are assistance in the form of fees given to students or students to help with their education. Likewise at Dharma Patra Vocational School, in this school there is also a scholarship program that is given to students who meet the requirements and criteria as scholarship recipients each semester, one of the criteria is students who get academic achievements such as getting class rankings. The Decision Support System (SPK) for determining scholarship recipients will process criteria data using the Analytcal Hierarchy Process (AHP) method. The assessment consists of several criteria, sub-criteria and alternatives. AHP is a form of decision support model with the main advantage of the equipment is a functional hierarchy. The AHP method is considered appropriate in assisting the decision-making process of determining scholarships because AHP can help determine the priority of several criteria by conducting pairwise comparison analysis of each criterion and sub-criteria. Thus, it is hoped that the results of this study will help the decision-making process to determine scholarship recipients.